2013
DOI: 10.1152/ajpheart.00618.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin G deficiency decreases complexity of atherosclerotic lesions in apolipoprotein E-deficient mice

Abstract: Rafatian N, Karunakaran D, Rayner KJ, Leenen FH, Milne RW, Whitman SC. Cathepsin G deficiency decreases complexity of atherosclerotic lesions in apolipoprotein E-deficient mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…CatG may either promote apoptosis [34, 35], or inhibit this process via Ang-II production [36]. Prior study from CatG-insufficient Apoe −/− Ctsg +/− mice demonstrated reduced apoptosis in atherosclerotic lesions [21]. However, TUNEL staining showed increased apoptosis in atherosclerotic lesions from Ldlr −/− Ctsg −/− mice at both the 3- and 6-month time points (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CatG may either promote apoptosis [34, 35], or inhibit this process via Ang-II production [36]. Prior study from CatG-insufficient Apoe −/− Ctsg +/− mice demonstrated reduced apoptosis in atherosclerotic lesions [21]. However, TUNEL staining showed increased apoptosis in atherosclerotic lesions from Ldlr −/− Ctsg −/− mice at both the 3- and 6-month time points (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanistic studies presented here disclose a heretofore unrecognized role for CatG in the regulation of plasma total and LDL cholesterol levels directly by degrading apoB on LDL (while not affecting HDL), although our study did not prove a role of CatG activity in Ang-II production in systolic or diastolic blood pressure changes during atherogenesis. A recent study using Apoe −/− Ctsg +/+ and CatG-haploinsufficient Apoe −/− Ctsg +/− mice suggested an insignificant contribution of CatG in atherosclerosis in these animals that accumulate primarily beta-VLDL rather than LDL [21]. CatG may behave differently depending on the type of hyperlipidemia, as does the cysteine protease cathepsin S (CatS) which we demonstrated significantly reduces atherosclerosis in CatS-deficient Ldlr −/− Ctss −/− mice [23], but not in Apoe −/− Ctss −/− mice (unpublished data) compared with corresponding CatS-sufficient control mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defective efferocytosis can result from phagocyte oxidative stress (due to reduced cholesterol efflux post-apoptotic cell engulfment [70]) and/or the cleavage of MerTK receptors by ADAM17, inhibiting the ability of efferocytes to engulf apoptotic cells [71]. A number of studies have identified other key players Cathepsin G and ERK5, in regulating efficient efferocytosis in atherosclerotic mouse models and necrotic core regions [72,73]. Consistent with previous observations [65], we observed that necroptotic macrophages are efferocytosed less effectively compared to apoptotic cells [61] which suggests that this may contribute directly to necrotic debris accumulaion in the plaque.…”
Section: Clearance and Removal Of Dead Cells: Efferocytosismentioning
confidence: 99%
“…Cathepsin L has been shown to be the major contributor to apoptosis of the macrophages resulting in necrotic core formation, leading to atherosclerotic plaque instability [195]. Interestingly, one recent study showed that cathepsin G deficiency attenuated the complexity of atherosclerotic lesions in apolipoprotein E-deficient mice via dampening apoptosis [196]. Cathepsin S, on the other hand, improves fibrous cap stabilization, and helps monocyte adhesion and migration in an in vitro system [197].…”
Section: Role Of Proteases In Cardiometabolic Diseasesmentioning
confidence: 99%